DIPG-35. OPEN DIPG INITIATIVE: A PLATFORM FOR ACCELERATING DISCOVERY THROUGH DATA ACCESS, CONSOLIDATION AND HARMONIZATION. (23rd April 2019) - Gaonkar, Krutika; Raman, Pichai; Kambhampati, Madhuri; Jones, Chris; Hawkins, Cynthia; Mueller, Sabine; Resnick, Adam; Nazarian, Javad
Abstract: Pediatric brain cancers remain amongst the most lethal childhood cancers with over five decades of failed clinical trials. However, precision based clinical trials incorporating upfront biopsies, postmortem biobanking, along with technological advancements have resulted in a remarkable surge of omics and molecular based tumor classifications as well as a fundamental revision of WHO grading of pediatric brain tumors. However clinical translation of such molecular advancements has yet to impact a broad range of pediatric brain cancers. Major factors contributing to this lag of translation include, data fragmentation across institution, lack of data harmonization, data access, computational limitation, and the paucity of linked clinical and molecular data. To address these obstacles, we set to develop a unique data sharing platform for diffuse intrinsic pontine glioma (DIPG); one of the most devastating childhood brain caners. This initiative, named Project Open DIPG (POP DIPG) intends to consolidate and harmonize DIPG omics across all exiting and newly developed molecular data. Here we report that an international collaboration lead by Children's Brain Tumor Tissue Consortium (CBTTC) has successfully launched POP DIPG housing the largest OMICs resource for DIPG and midline gliomas to date. Specifically POP DIPG houses the following molecular data: whole genome, whole exome, transcriptome, proteome, methylome of 850 unique subjects, over 1000 specimens and 20 avatar models of the disease. Harmonized and analyzed data are available through PedCBioportal providing the ease of access, rapid queries and hypothesis driven inquiries. Access to raw files is also granted though CBTTC to investigators with defined projects and hypotheses. With the expansion of POP DIPG, preclinical drug testing will be incorporated to accelerate discovery and more importantly to facilitate molecular-driven precision clinical trials. Open DIPG initiative will serve as a model for other challenging childhood cancers by bridging the current gap in bench to bedside translation.